Homoseksualne ofiary nazizmu i ich miejsce w kulturze pamięci = The homosexual victims of Nazism and their place in a culture of remembrance - Borysławska, Magda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The forgotten victims of Nazism are those, whose suffering was not acknowledged in the collective memory of a nation. The abovementioned category describes individuals persecuted on the ground of sexual orientation, both during the period of Third Reich and many years after its downfall. The research problem of the article is the approach towards the subject of gay persecution in the German historical narrative.
Keywords: nazizm; nieheteronormatywność; prześladowania gejów; dyskurs pamięci; nazism; non-heteronormativity; gay persecution; memory discourse